[11C]raclopride positron emission tomography study of dopamine‐D2/3 receptor binding in patients with severe major depressive episodes before and after electroconvulsive therapy and compared to control subjects. Issue 4 (7th February 2020) - Tiger, Mikael; Svensson, Jonas; Liberg, Benny; Saijo, Tomoyuki; Schain, Martin; Halldin, Christer; Farde, Lars; Lundberg, Johan
Abstract : Aim: The aim of the study was to test: (i) if D2 /D3 binding in three functional subsections of striatum is different in patients with severe major depressive episodes than in controls; and (ii) if this difference is normalized after electroconvulsive therapy (ECT). Methods: Nine inpatients were examined with positron emission tomography (PET) and the radioligand [ 11 C]raclopride before and after an average of 8.4 ECT sessions. Treatment response was assessed using the Montgomery–Åsberg Depression Rating Scale. Nine age‐ and sex‐matched controls were examined twice with PET and [ 11 C]raclopride. Results: [ 11 C]raclopride binding was significantly lower in all three subsections of striatum in patients compared to controls (Cohen's d z, 1.14–1.68; P = 0.003–0.027). Montgomery–Åsberg Depression Ratings decreased significantly after ECT ( P  < 0.001; Cohen's d z, 2.9). ECT had no statistically significant effect on [ 11 C]raclopride binding, although post‐ECT binding estimates were more similar to those obtained in controls in all subsections of striatum. Conclusion: Using PET and [ 11 C]raclopride, we found support for the notion that severe major depressive episodes are associated with significantly lower dopamine D2 /D3 binding in all three subsections of striatum compared to controls. We noted no significant effect on D2 /D3 binding in the patient group after response to ECT.